2021
DOI: 10.3389/fpls.2021.692564
|View full text |Cite
|
Sign up to set email alerts
|

Use of Phenomics for Differentiation of Mungbean (Vigna radiata L. Wilczek) Genotypes Varying in Growth Rates Per Unit of Water

Abstract: In the human diet, particularly for most of the vegetarian population, mungbean (Vigna radiata L. Wilczek) is an inexpensive and environmentally friendly source of protein. Being a short-duration crop, mungbean fits well into different cropping systems dominated by staple food crops such as rice and wheat. Hence, knowing the growth and production pattern of this important legume under various soil moisture conditions gains paramount significance. Toward that end, 24 elite mungbean genotypes were grown with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Genotypes with high water use index can serve as promising donors for improving wateruse efficiency in mungbean grown in soil with poor water holding capacity [38]. The large-scale phenomic studies were found promising for selecting the mungbean genotypes resistant to water stress [39]. In our study, photosynthetic ability remained unchanged which indicates relative resistance of cowpea plants to water stress.…”
Section: Plant Growthmentioning
confidence: 56%
“…Genotypes with high water use index can serve as promising donors for improving wateruse efficiency in mungbean grown in soil with poor water holding capacity [38]. The large-scale phenomic studies were found promising for selecting the mungbean genotypes resistant to water stress [39]. In our study, photosynthetic ability remained unchanged which indicates relative resistance of cowpea plants to water stress.…”
Section: Plant Growthmentioning
confidence: 56%
“…Other automated features of various HTP platforms are programmable watering to weight of plants to enable large-scale experiments requiring controlled watering levels. To our knowledge, few reports have evaluated transpiration and transpiration use efficiency (TUE) at the whole-plant level using mechanized gravimetrical methods [77,78], yet HTP has been successfully used to assess TUE in rice in response to salinity [37] and drought [79]. Moreover, open-source phenotyping technologies and off-shelf solutions are being established and becoming widespread, permitting easier practice and application for both researchers and farmers (e.g.…”
Section: High-throughput Phenotypingmentioning
confidence: 99%
“…Actual measured fresh biomass under stress (MWS, SWS) was used as a reference to predict the biomass from all the geometric parameters of each of the images acquired from three different views of the plants. This model was chosen based on the previous phenomics experiments [30].…”
Section: Growth Rates and Water Use Indexmentioning
confidence: 99%
“…Image-derived phenotyping of plants offer enormous potential for understanding functional features and estimating intricate traits, like yield, and their interaction with the unfavourable environmental conditions [25]. Throughout the past decade, phenomics has been a highly sought tool to precisely decipher the responses of field crops like wheat, barley, rice, mungbean and safflower for abiotic stresses [26][27][28][29][30]. However, there is little information regarding protocol and screening methodologies in the phenomics conditions for the tomato [31].…”
Section: Introductionmentioning
confidence: 99%